2018
DOI: 10.1016/j.ijid.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Scurvy as a mimicker of osteomyelitis in a child with autism spectrum disorder

Abstract: A case of scurvy in a 10-year-old boy with autism spectrum disorder is described. His clinical presentation was initially thought to be due to osteomyelitis, for which empirical antimicrobial therapy was initiated. Further invasive and ultimately unnecessary investigations were avoided when scurvy was considered in the context of a restricted diet and classic signs of vitamin C deficiency. Infectious diseases specialists should be aware of scurvy as an important mimicker of osteoarticular infections when invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…According to case reports of scurvy, in addition to fatigue, anemia, bruising, hematomas, and different types of pain, vitamin C deficiency has been associated with various cardiovascular symptoms [67,68,69,70,71,72,73,74,75,76], dyspnea [64,70,71,72,73,74,75,76,77,78,79,80,81], lower limb edema [13,64,66,70,72,80,160,161,162,163,164,165,166,167,168,169,170,171,172,173,174,175], infection-type symptoms [66,67,68,73,160,161,165,167,174,175,176,177], bleeding in the gastrointestinal and other regions [76,164,172,175,177,178,…”
Section: Discussionmentioning
confidence: 99%
“…According to case reports of scurvy, in addition to fatigue, anemia, bruising, hematomas, and different types of pain, vitamin C deficiency has been associated with various cardiovascular symptoms [67,68,69,70,71,72,73,74,75,76], dyspnea [64,70,71,72,73,74,75,76,77,78,79,80,81], lower limb edema [13,64,66,70,72,80,160,161,162,163,164,165,166,167,168,169,170,171,172,173,174,175], infection-type symptoms [66,67,68,73,160,161,165,167,174,175,176,177], bleeding in the gastrointestinal and other regions [76,164,172,175,177,178,…”
Section: Discussionmentioning
confidence: 99%
“…These include lethargy, irritability, arthralgia, and myalgia 6,7,20,67 . Follicular hyperkeratosis and ecchymosis/hemorrhage can occur as soon as 3 months after deficient vitamin C intake 7,9,67 …”
Section: Discussionmentioning
confidence: 99%
“…Literature reviewed yielded 77 cases of scurvy described in 65 published papers (Table S1), in addition to the two cases described here 1,8,9,11‐73 …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As food selectivity is the most common type of feeding difficulty in children with ASD, they are at risk of nutritional deficiencies, with resulting diverse health impacts. Studies have demonstrated that children with ASD had a greater number of nutritional deficiencies compared to typically developing children . Vitamin A, vitamin D and calcium deficiencies have been shown to be significantly more common in children with ASD with feeding difficulties .…”
Section: Health and Psychosocial Impacts Of Feeding Difficulties In Cmentioning
confidence: 99%